Virulence Factors and Antibiotic Resistance of Enterobacterales - Bujňáková, Dobroslava; Puvača, Nikola; Ćirković, Ivana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book compiles research on Enterobacterales characterization concerning the presence of genes associated with virulence (adhesins; surface cellulose structures and curli; siderophores, e.g., enterobactin, aerobactin, and yersiniabactin; protectines; invasins or toxins), and, furthermore, bacterial-biofilm-associated phenotypes. Although not directly involved in pathogenicity, the acquisition of multiple antibiotic resistances strongly supports the success of opportunistic Enterobacterales pathogens in invasion, survival, and spread and markedly complicates the treatment of infections. Not only pathogens, but also commensal bacteria, considered harmless and part of the normal microbiota, are exposed to selection pressure and can be a reservoir of mobile genetic elements carrying antibiotic resistance genes. Therefore, the occurrence of drug-resistant bacteria within a commensal population and the possibility to exchange genetic material through horizontal gene transfer may represent a major health concern.